2003
DOI: 10.1046/j.1600-0447.2003.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Lycanthropy – psychopathological and psychodynamical aspects

Abstract: Lycanthropy is interpreted by the authors as a delusion in the sense of the self-identity disorder defined by Scharfetter. It is mainly found in affective and schizophrenic disorders but can be a symptom of other psychiatric disorders as well. Psychodynamically this kind of delusion can be interpreted as an attempt to project suppressed affects, especially with aggressive or sexual content, into the figure of an animal. Psychotherapy and/or neuroleptic medication can be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, these theories do not explain the increased frequency of patients presenting to the ED with violent and acute behavioural disturbance during the full moon. Some of these patients attacked the staff like animals — biting, spitting and scratching — and one might compare them with werewolves of the past, who are said to have also appeared during the full moon 14 , 15 . It has been reported that the practice of rubbing magic ointment on the skin or inhaling vapour from a magic potion by an alleged lycanthrope induces metamorphosis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these theories do not explain the increased frequency of patients presenting to the ED with violent and acute behavioural disturbance during the full moon. Some of these patients attacked the staff like animals — biting, spitting and scratching — and one might compare them with werewolves of the past, who are said to have also appeared during the full moon 14 , 15 . It has been reported that the practice of rubbing magic ointment on the skin or inhaling vapour from a magic potion by an alleged lycanthrope induces metamorphosis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Lycanthropy is a topic of controversy in psychiatry. Some attribute it to misidentification syndromes and believe in its probable neuropsychiatric bases (4), but the most dominant idea describes it as a rare symptom which could be found in various psychiatric disorders, mostly in mood disorders and schizophrenia (2). So, lycanthropy has been known as a type of delusional symptom which is not specific for a special disorder (5).…”
Section: Discussionmentioning
confidence: 99%
“…In current medical literature, man–animal metamorphoses other than wolf and were wolf includes: gerbil, rabbit, horse, tiger, cat, bird, frog and bee. The Greeks also spoke of kynanthropy (kynior = dog) as the belief in being transformed into a dog (1, 2). In the psychiatric literature, lycanthropy is an unusual belief or delusion that one has been transformed into an animal or his/her behaviours or feelings are suggestive of such belief (3).…”
Section: Introductionmentioning
confidence: 99%
“…2 In most of the literature, subjects with this phenomenon report the metamorphosis in relationship to self. Nejad 3 reported a case of lycanthropy variant in which the subject reported the belief that he converted someone other than self to an animal.…”
mentioning
confidence: 99%